The Association of Demographic Characteristics and Top Management Team Heterogeneity on Hospital Performance - Prasetyo, Awal; Isa, Muzakar; Sutrisna, EM (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2023)
This study aims to show how the demographic characteristics and heterogeneity of the top management team (TMT) associate with hospital’s performance as measured by the balanced scorecard (BSC). The study employs cross-sectional primary data from hospitals in Central Java Indonesia, collected from 242 hospitals. The result shows that the demographic characteristics including age, female, period of experience serving as TMT, level and specialization of education, were not associated with the hospital’s performance. Likewise, the short period of experience in the organization inside or outside of a hospital’s TMT members was not associated with the hospital’s performance. However, TMT’s heterogeneity showed a positive result towards the hospital’s performance. The academic and practical implications of the findings are discussed.